KEBANGKRUTAN GENERAL MOTOR CORPORATION Karena krisis keuangan global atau karena in-efisiensi ? (Studi Kasus Prediksi Kebangkrutan General Motor Corporation menggunakan Altman Z-Score Analysis) - Andy Yulius (Universitas Bunda Mulia, 2017)
Global economic crisis has caused panic among industrial practitioners in term of their business life, not excluding the biggest car industry in the United States, General Motor Corporation which was eventually declared bankrupt. This case study focuses on bankruptcy detection using Professor Altman’s Z-score analysis where supportive elements of work efficiency reflected in a company’s financial report is also taken into account. Keyword: Bangkrupt, Z-Score